Roux-en-Y gastric bypass stands the test of time: 5-year results in low body mass index (30–35 kg/m2) Indian patients with type 2 diabetes mellitus - Lakdawala, Muffazal; Shaikh, Shehla; Bandukwala, Saifee; Remedios, Carlyne; Shah, Miloni; Bhasker, Aparna Govil (Surgery for obesity and related diseases, 2013)
Our objective was to evaluate the long-term results of laparoscopic Roux-en-Y gastric bypass on excess weight loss, remission of the metabolic syndrome, and complications in Indian patients with uncontrolled type 2 diabetes mellitus (T2DM) with a body mass index of 30–35 kg/m2. The setting was a corporate hospital in Mumbai, India. The present prospective observational study was begun in January 2006. A total of 52 patients with uncontrolled T2DM and a body mass index of 30–35 kg/m2 elected to undergo laparoscopic Roux-en-Y gastric bypass. The duration of T2DM was 3.5–14.5 years (median 8.4). Of the 52 patients, 61.5% had hypertension and 59.6% had dyslipidemia. Remission of T2DM and other components of the metabolic syndrome were assessed. All patients were followed up for 5 years. The median percentage of excess weight loss was 72.2% at 1 year and 67.8% at 5 years. Of the 52 patients, 84.6% had achieved euglycemia and 73.1% had achieved complete remission, 23.1% partial remission, and 3.84% no remission at 1 year. Weight regain occurred in 8 patients. They required antihypertensive drugs and statins, decreasing the complete remission rate to 57.7% and partial remission rate to 38.5% at 5 years. However, 96.2% improvement in metabolic status was found at the end of 5 years. Laparoscopic Roux-en-Y gastric bypass is a safe, efficacious, and cost-effective treatment for uncontrolled T2DM in patients with a body mass index of 30–35 kg/m2. Early-onset T2DM, better weight loss, and greater C-peptide levels were predictors of success after surgery. The improvement after surgery in hyperglycemia, hypertension, and dyslipidemia could help in controlling the occurrence of micro- and macrovascular complications and decrease the morbidity and mortality associated with T2DM.